Pre-lithiated silicon monoxide-based negative electrode material and preparation method thereof, negative electrode and lithium-containing battery
By preparing prelithiated silicon oxide-based negative electrode material, prelithiated silicon oxide-based particles with core-shell structure are solved by using solid-phase homogeneity treatment and spray granulation technology of metal lithium and silicon oxide powder. The problems of low efficiency and poor cycle stability of the negative electrode material of lithium-ion batteries achieve higher energy density and longer life, and simplify the process and reduce costs.
Patent Information
- Application Number
- CN202310721148.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2024-12-17
AI Technical Summary
The existing lithium-ion battery anode materials have low efficiency and poor cycle stability during the first cycle, resulting in insufficient energy density and lifespan, and the prelithiation process is complex and costly, making it difficult to promote.
The preparation method of prelithiated silicon oxide-based negative electrode material is adopted, and the solid phase homogenization of metal lithium and silicon oxide powder is added, solid dispersant and carbon source are added, spray granulation and thermal stabilization are carried out to form a core. The prelithiated silicon oxide-based particles in the shell structure improve the introduction and dispersion of lithium elements.
It improves the first Coulomb efficiency and cycle stability of the negative electrode material, reduces the instability of lithium content, simplifies the process, reduces costs, and is compatible with the existing battery system.
Smart Images

Figure CN119153637A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to lithium-ion battery materials, and in particular, to a pre-lithiated silicon oxide-based negative electrode material and a preparation method thereof, a negative electrode and a lithium-containing battery. Background Art
[0002] In recent years, with the rapid development of new energy vehicles, smart grids, and distributed energy storage, the development of lithium-ion batteries with high energy density, high safety, and long cycle life has become a research hotspot in the field of energy storage. The improvement of battery energy density mainly depends on the development of key electrode materials, such as the continuous improvement of the capacity of positive and negative electrode materials. The capacity of existing lithium-ion battery negative electrode materials has reached its limit. In order to meet the energy needs of the new generation and improve the energy density of batteries, it is of great significance to develop new lithium battery negative electrode materials.
[0003] Among the new negative electrode materials, silicon materials have attracted much attention due to their high theoretical capacity, abundant reserves, and low discharge voltage. However, silicon materials have a huge volume expansion (greater than 300%) during the process of lithium insertion and extraction, which causes the negative electrode materials to pulverize and fall off, forming "dead silicon", and eventually causing the negative electrode materials to lose electrical contact and cause the battery to fail. Secondly, repeated volume expansion and contraction will also cause the SEI film on the surface to be continuously destroyed and generated, continuously consuming the positive electrode's Li + , resulting in a decrease in the battery coulombic efficiency. These problems ultimately lead to a sharp deterioration in the battery cycle performance, seriously affecting the battery life.
[0004] Compared with nano-silicon, although silicon oxide sacrifices some capacity, its volume expansion is relatively small (about 100%), and the byproducts such as lithium oxide, lithium silicate, and lithium metasilicate generated during the charge and discharge process can act as buffer media to improve the material's cycle performance, which has attracted widespread attention from academia and industry. However, silicon oxide materials have a large irreversible capacity loss in the first cycle, and the first coulomb efficiency is low (about 65%), resulting in the loss of a large amount of lithium ions in the first cycle, reducing the battery's energy density and cycle life, which seriously restricts the application of silicon oxide-based materials in high-energy lithium-ion batteries.
[0005] Pre-lithiation technology provides an effective solution to solve the irreversible capacity loss and improve the coulombic efficiency. Pre-lithiation technology can be divided into powder pre-lithiation and pole piece pre-lithiation, mainly including lithium supplement additives, stable metal lithium powder, electrochemical pre-lithiation, contact short circuit reaction, chemical pre-lithiation, etc. At present, the problem of low initial efficiency of silicon negative electrode is mostly solved by pre-lithiation at the pole piece level, but we should realize that the pre-lithiation process at the pole piece level needs to increase the pre-lithiation process steps and the corresponding equipment and environmental space. This will greatly increase the time cost, equipment investment cost and plant renovation cost of lithium battery manufacturing, which is not conducive to the promotion and use of silicon negative electrode materials, and hinders the development of lithium batteries towards higher energy density and longer life. In addition, the current pre-lithiation method still has many difficulties to be overcome in practical applications, such as complex process, harsh preparation conditions, poor compatibility with existing battery systems, poor operability and other problems.
[0006] Powder pre-lithiation is the most direct and effective means to improve the first coulombic efficiency of silicon negative electrode. By introducing exogenous lithium into the battery system in a suitable manner and form, it is used to improve the reduction in the first coulombic efficiency caused by the consumption of effective lithium by the silicon negative electrode. However, it is currently difficult to increase the lithium content of powder pre-lithiation. When the lithium content is high, the lithium on the surface of the material makes the material itself unstable and difficult to preserve. In addition, it is easy to cause the slurry pH to increase during the slurrying process when used, and react with the binder and / or solvent water to produce gas that is difficult to slurry, which in turn causes the battery performance to deteriorate. Therefore, optimizing the structure and preparation process conditions of powder pre-lithiation and forming a preparation method compatible with the existing battery system is the key to improving the electrochemical performance of silicon-based negative electrode materials. Summary of the invention
[0007] The purpose of the present invention is to provide a pre-lithiated silicon oxide-based negative electrode material and a preparation method thereof, a negative electrode and a lithium-containing battery, so as to solve the technical problems of low initial coulombic efficiency and poor cycle stability of the negative electrode material.
[0008] In order to achieve the above-mentioned objectives, the first aspect of the present disclosure provides a method for preparing a pre-lithiated silicon oxide-based negative electrode material, comprising the following steps: (1) contacting metallic lithium with silicon oxide powder and performing solid phase homogenization treatment to obtain a first product; (2) dispersing and homogenizing the first product with a solid dispersant to obtain a second product; (3) contacting the second product with a carbon source and a solvent and performing mixing and homogenization treatment to obtain a mixed slurry; (4) spray granulating the mixed slurry to obtain a third product; (5) thermally stabilizing the third product; wherein the above steps (1) to (5) are performed in an inert atmosphere.
[0009] Optionally, in step (1), the weight ratio of the metallic lithium to the silicon dioxide powder is 1:1 to 100, preferably 1:20 to 100;
[0010] Optionally, the metallic lithium is selected from one or more of lithium ingots, lithium wires, lithium powders and lithium sheets;
[0011] Optionally, the average particle size of the silicon oxide powder is 0.1 to 20 μm.
[0012] Optionally, in step (1), the solid phase homogenization treatment method includes mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser;
[0013] Optionally, the conditions for the solid phase homogenization treatment include: a ball milling speed of 300 to 2000 r / min, a ball milling time of 6 to 72 h, and a ball-to-material ratio of 1 to 20:1; preferably, the ball milling speed is 500 to 1000 r / min, the ball milling time is 6 to 48 h, and the ball-to-material ratio is 10 to 20:1.
[0014] Optionally, in step (2), the weight ratio of the solid dispersant to metallic lithium is 0.1 to 50:1, preferably 5 to 10:1;
[0015] Optionally, the solid dispersant is selected from one or more of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon and soft carbon.
[0016] Optionally, in step (2), the dispersion and homogenization treatment method includes mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser;
[0017] Optionally, the conditions for the dispersion and homogenization treatment include: a ball milling speed of 50 to 500 r / min, a ball milling time of 0.5 to 12 h, and a ball-to-material ratio of 1 to 20:1; preferably, the ball milling speed is 100 to 300 r / min, the ball milling time is 3 to 8 h, and the ball-to-material ratio is 10 to 20:1.
[0018] Optionally, in step (3), the carbon source is selected from a carbonizable organic carbon source; the weight ratio of the carbon source to metallic lithium is 1 to 60:1, preferably 10 to 30:1;
[0019] The weight ratio of the solvent to the carbon source is 10 to 100:1, preferably 50 to 100:1;
[0020] Optionally, the solid content of the mixed slurry is 1 to 30% by weight, preferably 5 to 15% by weight;
[0021] Optionally, the carbonizable organic carbon source is selected from one or more of a polymer carbon source, a petroleum carbon source, a sugar carbon source, a graphite carbon source and other carbon sources;
[0022] The polymer carbon source includes one or more of phenolic resin, epoxy resin, polyvinyl pyrrolidone and polyvinyl alcohol;
[0023] The petroleum carbon source includes one or more of asphalt, petroleum coke and needle coke;
[0024] The sugar carbon source includes one or more of glucose, sucrose and fructose;
[0025] The other carbon source is selected from one or more of sodium carboxymethyl cellulose, polyvinyl alcohol and carboxy styrene butadiene latex; preferably one or more of sodium methyl cellulose and polyvinyl alcohol;
[0026] The solvent is selected from one or more of ethanol, isopropanol, n-butanol, cyclohexane and cyclohexanone.
[0027] Optionally, in step (3), the mixing and homogenizing treatment comprises mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser;
[0028] Optionally, the conditions for the mixing homogenization treatment include: a ball milling speed of 50 to 500 r / min, a ball milling time of 0.5 to 24 h, and a ball-to-material ratio of 1 to 20:1; preferably, a ball milling speed of 100 to 300 r / min, a ball milling time of 0.5 to 3 h, and a ball-to-material ratio of 10 to 20:1.
[0029] Optionally, in step (4), the conditions of the spray granulation treatment include: an inlet temperature of 100 to 300° C., an outlet temperature of 50 to 200° C., a carrier gas flow rate of 10 to 100 L / min, and a pressure of -0.1 to -0.05 MPa;
[0030] Preferably, the inlet temperature is 120 to 240°C, the outlet temperature is 80 to 150°C, the carrier gas flow rate is 30 to 60 L / min, and the pressure is -0.08 to -0.05 MPa;
[0031] The carrier gas is selected from one or more of argon, nitrogen and helium;
[0032] Preferably, the average particle size of the third product obtained by spray granulation is 5 to 50 μm.
[0033] Optionally, in step (5), the thermal stabilization treatment includes a multi-stage sintering treatment;
[0034] Preferably, the heat stabilization treatment includes a first stage sintering treatment and a second stage sintering treatment performed sequentially; wherein the conditions of the first stage sintering treatment include: heating to 200-500°C at a heating rate of 1-5°C / min, and then maintaining the temperature for 1-6 hours; the conditions of the second stage sintering treatment include: heating to 600-1200°C at a heating rate of 2-5°C / min, and then maintaining the temperature for 1-12 hours;
[0035] Preferably, the conditions for the first sintering treatment include: heating to 250-400°C at a heating rate of 2-3°C / min, and then maintaining the temperature for 2-3 hours; the conditions for the second sintering treatment include: heating to 700-900°C at a heating rate of 3-5°C / min, and then maintaining the temperature for 2-6 hours.
[0036] A second aspect of the present disclosure provides a pre-lithiated silicon oxide-based negative electrode material prepared according to the method described in the first aspect of the present disclosure.
[0037] A third aspect of the present disclosure provides a pre-lithiated silicon oxide-based negative electrode material, the pre-lithiated silicon oxide-based negative electrode material comprising pre-lithiated silicon oxide-based particles with a core-shell structure; the pre-lithiated silicon oxide-based particles comprising an inner core and a first carbon layer and a second carbon layer sequentially coated on the outer surface of the inner core from the inside to the outside, the first carbon layer and the second carbon layer forming an outer shell of the core-shell structure; wherein the inner core comprises a silicon oxide matrix and an inner core lithium-containing component dispersed on the surface and in the pores of the silicon matrix; the inner core lithium-containing component comprises lithium silicate.
[0038] Optionally, the first carbon layer comprises a first lithium-containing component, and the second carbon layer is lithium-free; the lithium content in the core is greater than the lithium content in the first carbon layer;
[0039] Preferably, the content of the lithium-containing component in the pre-lithiated silicon oxide-based particles is 0.01 to 10% by weight, preferably 0.1 to 6% by weight, based on the total amount of lithium element;
[0040] Optionally, the core lithium-containing component further comprises metallic lithium;
[0041] The first lithium-containing component comprises one or more of metallic lithium, lithium oxide and lithium-carbon alloy.
[0042] Optionally, based on the total weight of the pre-lithiated silicon dioxide-based particles, the content of the inner core is 50-95% by weight, preferably 60-90% by weight; the total content of the outer shell is 5-50% by weight, preferably 5-40% by weight.
[0043] Optionally, the pre-lithiated silicon oxide-based particles have an average particle size of 0.5 to 30 μm and a BET specific surface area of 0.1 to 100 m 2 / g, total pore volume is 0.001~0.5cm 3 / g;
[0044] Optionally, the total thickness of the first carbon layer and the second carbon layer is 10-1000 nm; preferably, the thickness of the first carbon layer is 10-500 nm, and the thickness of the second carbon layer is 40-100 nm.
[0045] A fourth aspect of the present disclosure provides a negative electrode for a lithium-containing battery, which comprises the pre-lithiated silicon oxide-based negative electrode material described in the second aspect or the third aspect of the present disclosure.
[0046] A fifth aspect of the present disclosure provides a lithium-containing battery, comprising the negative electrode described in the fourth aspect of the present disclosure.
[0047] Through the above technical scheme, the present invention provides a pre-lithiated silicon oxide-based negative electrode material and a preparation method thereof, a negative electrode and a lithium-containing battery. The present invention uses silicon oxide and metallic lithium as raw materials, realizes the introduction of lithium through solid phase homogenization treatment, and uses silicon oxide with low specific capacity as a matrix, thereby reducing the volume expansion phenomenon of the negative electrode material during use; and by adding a solid dispersant for dispersion and homogenization, it is possible to avoid adhesion and agglomeration of silicon oxide and lithium during the reaction process, so that the silicon oxide-lithium particles are fully dispersed; at the same time, the dispersant can also form a dispersed conductive network, increase the conductivity of the particles, and inhibit The conductivity is reduced due to the introduction of lithium; the present invention is disclosed by spray granulation after being made into a slurry with a carbon source and a solvent, and the slurry formed by the pre-lithiation particles and the carbon source is quickly dried and formed, so that the carbon source can be evenly and tightly coated on the surface of the pre-lithiation particles, and the coating effect is more uniform and dense; finally, through thermal stabilization treatment, the introduced lithium element is continuously diffused into the silicon oxide, reacting with the silicon oxide to form a thermodynamically relatively stable lithium silicate to achieve pre-lithiation, while inhibiting the growth of silicon grains inside the silicon oxide particles, thereby improving the first coulomb efficiency and cycle stability of the silicon oxide negative electrode material. And this method has the characteristics of controllable lithium content, simple process, simple operation, environmentally friendly process, low cost, and easy scalability. It is compatible with the existing lithium ion battery negative electrode material system and can be directly applied to the existing lithium ion battery negative electrode material system.
[0048] The pre-lithiated silicon oxide-based negative electrode material provided by the present invention has a higher lithium content in the core, and can release more lithium during the charge and discharge cycle to improve the initial coulombic efficiency and cycle stability of the negative electrode material; the lithium-containing core is coated with two outer carbon layers, and there is no lithium on the surface of the negative electrode material. During the homogenization process, the pH of the slurry increases less and the gas production of the slurry is suppressed.
[0049] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0051] Figure 1 is an exemplary structural diagram of a pre-lithiated silicon oxide-based negative electrode material provided by the present disclosure;
[0052] Figure 2 is a scanning electron microscope photograph of the negative electrode material prepared in Example 1;
[0053] Figure 3 is a transmission electron microscope photograph of the negative electrode material prepared in Example 1;
[0054] Figure 4 is the X-ray diffraction pattern of the negative electrode material prepared in Example 1;
[0055] Figure 5 is the Li 1s X-ray photoelectron high-resolution scanning energy spectrum of the negative electrode material prepared in Example 1;
[0056] Figure 6 is the Li 1s X-ray photoelectron high-resolution scanning energy spectrum of the intermediate product prepared in Example 1;
[0057] Figure 7 This is the first charge and discharge curve of the negative electrode material using the product obtained in Example 1 at a current density of 0.2C;
[0058] Figure 8 is a cycle performance diagram of the negative electrode material using the product obtained in Example 1 at a current density of 0.2C;
[0059] Fig. 9 It is a capacity retention curve of the negative electrode material using the product obtained in Example 1 at a current density of 0.2C. DETAILED DESCRIPTION
[0060] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0061] The first aspect of the present disclosure provides a method for preparing a pre-lithiated silicon oxide-based negative electrode material, comprising the following steps:
[0062] (1) contacting metallic lithium with silicon oxide powder and performing solid phase homogenization to obtain a first product;
[0063] (2) dispersing and homogenizing the first product with a solid dispersant to obtain a second product;
[0064] (3) contacting the second product with a carbon source and a solvent and performing a mixing and homogenization treatment to obtain a mixed slurry;
[0065] (4) subjecting the mixed slurry to a spray granulation process to obtain a third product;
[0066] (5) subjecting the third product to a thermal stabilization treatment;
[0067] The above steps (1) to (5) are carried out in an inert atmosphere.
[0068] The present invention uses silicon oxide and metallic lithium as raw materials, realizes the introduction of lithium through solid phase homogenization treatment, adopts silicon oxide with low specific capacity as matrix, reduces the volume expansion phenomenon of negative electrode material in use; and by adding solid dispersant for dispersion and homogenization, it can avoid the adhesion and agglomeration of silicon oxide and lithium during the reaction, so that the silicon oxide-lithium particles are fully dispersed; at the same time, the dispersant can also form a dispersed conductive network, increase the conductivity of the particles, and inhibit the decrease in conductivity caused by the introduction of lithium; the present invention makes a slurry with a carbon source and a solvent and then spray granulates, and the slurry formed by pre-lithiation particles and carbon source is quickly dried and formed, and the carbon source can be evenly and tightly coated on the surface of pre-lithiation particles, and the coating effect is more uniform and dense; finally, through thermal stabilization treatment, the introduced lithium element is continuously diffused into silicon oxide, reacts with silicon oxide, forms thermodynamically relatively stable lithium silicate to realize pre-lithiation, and at the same time inhibits the growth of silicon grains inside silicon oxide particles, thereby improving the first coulombic efficiency and cycle stability of silicon oxide negative electrode material. The method has the characteristics of controllable lithium content, simple process, easy operation, environmentally friendly process, low cost and easy scalability. It is compatible with the existing negative electrode material system of lithium-ion batteries and can be directly applied to the existing negative electrode material system of lithium-ion batteries.
[0069] In a specific embodiment, the inert atmosphere comprises one or more of nitrogen, helium, neon, argon, krypton and xenon; the water content of the inert atmosphere is less than 0.1 wt%, and the oxygen content is less than 0.1 wt%.
[0070] In one embodiment, in step (1), the weight ratio of the metallic lithium to the silicon dioxide powder is 1:1-100.
[0071] In a preferred embodiment, the weight ratio of the metal lithium to the silicon oxide powder is 1:20 to 100. The preparation of the negative electrode material according to the preferred weight ratio of the metal lithium to the porous silicon oxide provided in the present disclosure is conducive to further improving the first coulombic efficiency and cycle stability of the negative electrode material.
[0072] In a specific embodiment, the average particle size of the silicon oxide powder is 0.1-20 μm. The silicon oxide powder used in the present disclosure can be purchased through conventional channels or prepared by known methods.
[0073] In a specific embodiment, the metallic lithium is selected from one or more of lithium ingots, lithium wires, lithium powders and lithium sheets.
[0074] In one embodiment, in step (1), the solid phase homogenization treatment method includes mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser.
[0075] In a preferred embodiment, the conditions for the solid phase homogenization treatment include: a ball milling speed of 300 to 2000 r / min, a ball milling time of 6 to 72 h, and a ball-to-material ratio of 1 to 20:1; preferably, the ball milling speed is 500 to 1000 r / min, the ball milling time is 6 to 48 h, and the ball-to-material ratio is 10 to 20:1.
[0076] In one embodiment, in step (2), the weight ratio of the solid dispersant to the metallic lithium is 0.1 to 50: 1, preferably 5 to 10: 1. Preparation according to the weight ratio provided in the present disclosure can avoid adhesion and agglomeration between particles, while also helping to control the weight and thickness of the first carbon layer in the product, thereby improving the performance of the final negative electrode material.
[0077] In a specific embodiment, the solid dispersant is selected from one or more of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon and soft carbon.
[0078] In one embodiment, in step (2), the dispersion and homogenization treatment comprises mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser.
[0079] In a preferred embodiment, the conditions for the dispersion and homogenization treatment include: a ball milling speed of 50 to 500 r / min, a ball milling time of 0.5 to 12 h, and a ball-to-material ratio of 1 to 20:1; preferably, the ball milling speed is 100 to 300 r / min, the ball milling time is 3 to 8 h, and the ball-to-material ratio is 10 to 20:1.
[0080] In one embodiment, in step (3), the carbon source is selected from a carbonizable organic carbon source; the weight ratio of the carbon source to metallic lithium is 1 to 60:1, preferably 10 to 30:1; the weight ratio of the solvent to the carbon source is 10 to 100:1, preferably 50 to 100:1;
[0081] Optionally, the solid content of the mixed slurry is 1 to 30% by weight, preferably 5 to 15% by weight.
[0082] In one embodiment, the carbonizable organic carbon source is selected from one or more of a polymer carbon source, a petroleum carbon source, a sugar carbon source, a graphite carbon source and other carbon sources.
[0083] In a specific embodiment, the polymer carbon source includes one or more of phenolic resin, epoxy resin, polyvinyl pyrrolidone and polyvinyl alcohol;
[0084] The petroleum carbon source includes one or more of asphalt, petroleum coke, and needle coke;
[0085] The sugar carbon source includes one or more of glucose, sucrose and fructose;
[0086] The other carbon source is selected from one or more of sodium carboxymethyl cellulose, polyvinyl alcohol and carboxy styrene butadiene latex; preferably one or more of sodium methyl cellulose and polyvinyl alcohol;
[0087] The solvent is selected from one or more of ethanol, isopropanol, n-butanol, cyclohexane and cyclohexanone.
[0088] In one embodiment, in step (3), the mixing and homogenizing treatment comprises mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser.
[0089] In a preferred embodiment, the conditions for the mixing and homogenizing treatment include: a ball milling speed of 50 to 500 r / min, a ball milling time of 0.5 to 24 h, and a ball-to-material ratio of 1 to 20:1; preferably, the ball milling speed is 100 to 300 r / min, the ball milling time is 0.5 to 3 h, and the ball-to-material ratio is 10 to 20:1.
[0090] In one embodiment, in step (4), the conditions of the spray granulation treatment include: an inlet temperature of 100 to 300°C, an outlet temperature of 50 to 200°C, a carrier gas flow rate of 10 to 100 L / min, and a pressure of -0.1 to -0.05 MPa.
[0091] In a preferred embodiment, the inlet temperature is 120-240°C, the outlet temperature is 80-150°C, the carrier gas flow rate is 30-60 L / min, and the pressure is -0.08 to -0.05 MPa.
[0092] The present invention adopts the mixed slurry for spray granulation, which is beneficial to improve the uniformity of the second carbon layer coating and avoid damage to the particle pore structure. The present invention can adopt conventional spray granulation devices in the art for spray granulation.
[0093] In a specific embodiment, the average particle size of the third product obtained by spray granulation is 5 to 50 μm.
[0094] In one embodiment, in step (5), the thermal stabilization treatment includes a multi-stage sintering treatment;
[0095] Preferably, the thermal stabilization treatment includes a first stage sintering and a second stage sintering; wherein the temperature of the first stage sintering is 200-500°C, the heating rate is 1-5°C / min, and the time is 1-6h; the temperature of the second stage sintering is 600-1200°C, the heating rate is 2-5°C / min, and the time is 1-12h;
[0096] In a preferred embodiment, the temperature of the first sintering stage is 2-3°C, the heating rate is 250-400°C / min, and the time is 2-3h; the temperature of the second sintering stage is 3-5°C, the heating rate is 700-900°C / min, and the time is 2-6h. Thermal stabilization is carried out by sintering at a staged temperature, and the thermal stabilization temperature is limited to the above range, which can further inhibit the growth of silicon grains inside silicon particles and further prevent the decrease of cycle stability; and it also helps the lithium element to migrate into the silicon oxide core and react with silicon oxide to form lithium silicate.
[0097] A second aspect of the present disclosure provides a pre-lithiated silicon oxide-based negative electrode material prepared according to the method described in the first aspect.
[0098] The third aspect of the present disclosure provides a pre-lithiated silicon oxide-based negative electrode material, wherein the pre-lithiated silicon oxide-based negative electrode material comprises pre-lithiated silicon oxide-based particles of a core-shell structure; the pre-lithiated silicon oxide-based particles comprise a core and a first carbon layer and a second carbon layer sequentially coated from the inside to the outside on the outer surface of the core, wherein the first carbon layer and the second carbon layer form an outer shell of the core-shell structure;
[0099] The core comprises a silicon oxide matrix and a core lithium-containing component dispersed on the surface and in the pores of the silicon matrix; the core lithium-containing component comprises lithium silicate.
[0100] The pre-lithiated silicon oxide-based negative electrode material provided by the present invention has a higher lithium content in the core, and can release more lithium during the charge and discharge cycle to improve the initial coulombic efficiency and cycle stability of the negative electrode material; the lithium-containing core is coated with two outer carbon layers, and there is no lithium on the surface of the negative electrode material. During the homogenization process, the pH of the slurry will not increase, thereby inhibiting the gas production of the slurry.
[0101] In the present disclosure, the general chemical formula of lithium silicate in the core is LiSi x O y Schematically represented, wherein 0<x≤10, 0<y≤10. The values of x and y are determined by XRD.
[0102] In one embodiment, the first carbon layer comprises a first lithium-containing component, and the second carbon layer is lithium-free; the lithium content in the inner core is greater than the lithium content in the first carbon layer.
[0103] In one embodiment, the content of the lithium-containing component in the pre-lithiated silicon oxide-based particles is 0.01 to 10% by weight, preferably 0.1 to 6% by weight, based on the total amount of lithium. When the lithium content of the pre-lithiated silicon oxide-based negative electrode material is within the range of this embodiment, it is beneficial to improve the first coulombic efficiency and cycle capacity retention rate of the negative electrode material.
[0104] In a specific embodiment, based on the total amount of lithium element, the content of the lithium-containing component in the core is 20 to 70% by weight, preferably 50 to 70% by weight; the content of the first lithium-containing component is 0 to 20% by weight, preferably 10 to 20% by weight;
[0105] Optionally, the core lithium-containing component further comprises metallic lithium;
[0106] The first lithium-containing component comprises one or more of metallic lithium, lithium oxide and lithium-carbon alloy.
[0107] The pre-lithiated silicon oxide-based negative electrode material provided by the present invention has a gradient distribution in which the lithium content decreases in the order of inner core-first carbon layer-second carbon layer, wherein the inner core has the highest lithium content, which is beneficial to improving the capacity cycle stability; the second carbon layer is lithium-free, which can further avoid the increase of the pH value of the slurry during the homogenization process and inhibit the gas production of the slurry.
[0108] In one embodiment, based on the total weight of the pre-lithiated silicon dioxide-based particles, the content of the core is 50-95% by weight, preferably 60-90% by weight; the total content of the shell is 5-50% by weight, preferably 5-40% by weight.
[0109] In one embodiment, based on the total weight of the pre-lithiated silicon oxide-based particles, the content of the first carbon layer is 1 to 30 weight %, preferably 10 to 30 weight %; the content of the second carbon layer is 1 to 20 weight %, preferably 10 to 20 weight %.
[0110] In one embodiment, the pre-lithiated silicon oxide-based particles have an average particle size of 0.5 to 30 μm, an average pore size of 1 to 50 nm, and a BET specific surface area of 0.1 to 100 m 2 / g, total pore volume is 0.001~0.5cm 3 / g;
[0111] Optionally, the total thickness of the first carbon layer and the second carbon layer is 10 to 1000 nm; preferably, the thickness of the first carbon layer is 10 to 500 nm, and the thickness of the second carbon layer is 40 to 100 nm. The thickness of the first carbon layer and the second carbon layer in the present disclosure can be obtained by a transmission electron microscope photograph of the negative electrode material of the material.
[0112] A fourth aspect of the present disclosure provides a negative electrode for a lithium-containing battery, which comprises the pre-lithiated silicon oxide-based negative electrode material described in the second aspect or the third aspect of the present disclosure.
[0113] According to the present disclosure, the negative electrode can be prepared by a method known in the art. For example, the negative electrode is obtained by slurry coating, and the slurry includes the pre-lithiated silicon oxide-based negative electrode material provided by the present disclosure, a conductive agent, a binder, etc., and the conductive agent, the binder, and other reagents are conventionally selected in the art.
[0114] A fifth aspect of the present disclosure provides a lithium-containing battery, which includes the negative electrode described in the fourth aspect of the present disclosure.
[0115] According to the present disclosure, a lithium-containing battery can be assembled using methods known in the art.
[0116] The pre-lithiated silicon oxide-based negative electrode material provided by the present disclosure can be directly applied to the existing lithium-containing battery system, and can also be used in combination with lithium-ion battery graphite negative electrode materials, silicon-carbon negative electrode materials, silicon oxide negative electrode materials, etc. When the prepared high-stability pre-lithiated silicon oxide-based negative electrode material is applied to lithium-ion batteries, the first coulombic efficiency and cycle stability of lithium-ion batteries are significantly improved.
[0117] The present disclosure is further illustrated below by way of examples, but the present disclosure is not limited thereby.
[0118] In the following examples, unless otherwise specified, the raw materials used are commercially available products.
[0119] In the following examples, the specific testing methods are as follows:
[0120] The average particle size was measured using an optical particle size analyzer, the instrument model being Mastersizer 3000;
[0121] The SEM test method is scanning electron microscope, and the instrument model is S4800 of Hitachi, Japan;
[0122] The XRD test method is an X-ray diffractometer, and the instrument model is the X'Pert PRO powder X-ray diffractometer from PANalytical;
[0123] The XPS test method is X-ray photoelectron spectrometer, and the instrument model is VG ESCALAB;
[0124] The test method for electrochemical cycle performance is the blue electric test system, and the instrument model is CT3001A.
[0125] The spray granulation device was BUCHI Mini Spray Dryer B-290.
[0126] Example 1
[0127] In an inert environment without water or oxygen, 2g of silicon dioxide powder and 0.02g of metal lithium ingot (the weight ratio of metal lithium to silicon dioxide powder is 1:100) are weighed and placed in a zirconium oxide ball milling jar, which is sealed and transferred to a planetary ball mill for ball milling. The ball-to-material ratio of the ball milling is 20:1, the diameters of the zirconium balls are 5.5mm, 3.0mm, and 2.0mm, respectively, and the ratio is 2:5:3. The ball milling speed is 500 rpm and the ball milling time is 12 hours. Then 0.1g of natural graphite (the weight ratio of solid dispersant to metal lithium is 5:1) is added and the ball milling is continued at a speed of 450 rpm for 2 hours. 0.2g sodium carboxymethyl cellulose and 1.0g asphalt (the weight ratio of carbon source to metal lithium is 60:1), and 30g solvent cyclohexane (the weight ratio of solvent to carbon source is 25:1) are added, the ball milling speed is 450 rpm, the ball milling time is 2 hours, and a mixed slurry is obtained, and the solid content in the mixed slurry is 11% by weight. The mixed slurry is spray granulated, the inlet temperature is 180°C, the outlet temperature is 90°C, argon gas is used as carrier gas, the carrier gas flow rate is 40L / min, and the pressure is -0.05MPa, to obtain a lithium-containing silicon oxide-based negative electrode material precursor. The lithium-containing silicon oxide material precursor is placed in a tubular furnace under an argon atmosphere for thermal stabilization and two-stage sintering treatment: first, the temperature is increased to 450°C at a rate of 2°C / min, and then the temperature is maintained for 2h, and preheating and stabilization is performed; then the temperature is increased to 900°C at a heating rate of 5°C / min, and then the temperature is maintained for 2h. After cooling to room temperature, the material was discharged to obtain a pre-lithiated silicon 2 oxide negative electrode material, which was recorded as F-1.
[0128] The scanning electron microscope photo of product F-1 is shown in Figure 2 As shown by Figure 2 It can be seen that the pre-lithiation silicon oxide-based negative electrode material is granular with uniform particle size and good dispersion.
[0129] The transmission electron microscope photo of product F-1 is as follows Figure 3 As shown by Figure 3 It can be seen that the F-1 pre-lithiated silicon oxide-based negative electrode material has two dense carbon coating layers, the thickness of the first carbon layer is in the range of 20 to 40 nm, and the thickness of the second carbon layer is in the range of 20 to 40 nm.
[0130] The X-ray diffraction pattern of product F-1 is as follows Figure 4 As shown by Figure 4It can be seen that a sharp carbon peak appears in the F-1 pre-lithiated silicon oxide-based negative electrode material, indicating that the powder gradient pre-lithiated silicon oxide-based composite material is densely coated with a carbon layer. In addition to the silicon oxide peak package, the spectrum also shows obvious lithium salt Li2Si2O5 characteristic peaks and silicon characteristic peaks, indicating that lithium is successfully introduced into the silicon oxide-based material and thermodynamically relatively stable lithium silicates and silicon-lithium alloys are formed to achieve pre-lithiation.
[0131] The Li 1s X-ray photoelectron high-resolution scanning spectrum of product F-1 is shown in Figure 5 As shown by Figure 5 It can be seen that the characteristic peak of Li does not appear in the spectrum; and the Li1s X-ray photoelectron high-resolution scanning spectrum of the intermediate product after adding natural graphite solid dispersant for ball milling in this embodiment is as follows Figure 6 As shown, Figure 6 The sharp characteristic peak of Li appears in the graph, indicating that the lithium content of the multi-stage coated negative electrode material F-1 provided in this embodiment is distributed in a gradient, especially that the surface of the negative electrode material does not contain lithium.
[0132] The electrochemical capacity-voltage test results of product F-1 assembled into a lithium-ion battery as a negative electrode material (current density is 0.2C) are as follows Figure 7 As shown by Figure 7 It can be seen that the first charge specific capacity is 380.4mAh / g, the first discharge specific capacity is 455.6mAh / g, and the first coulombic efficiency is 83.5%, indicating that the first charge specific capacity and the first coulombic efficiency of the battery are relatively high; the relationship between the number of battery cycles and the specific capacity is shown in the figure below: Figure 8 As shown by Figure 8 It can be seen that as the charge and discharge process proceeds, the battery specific capacity gradually increases and stabilizes at around 450mAh / g; and the battery capacity retention rate after 400 cycles (such as Fig. 9 As shown in the figure, the content of α-ketoplastomer (α-ketoplastomer) is still greater than 100%, which shows good cycle stability.
[0133] Comparative Example 1
[0134] Compared with Example 1, this comparative example only performs a layer of carbon coating, specifically comprising the following steps:
[0135] In an inert environment without water and oxygen, 2g of silicon dioxide powder and 0.02g of metal lithium ingot (the weight ratio of metal lithium to silicon dioxide powder is 1:100) are weighed and placed in a zirconium oxide ball milling jar, which is sealed and transferred to a planetary ball mill for ball milling. The ball-to-material ratio of the ball milling is 20:1, the diameters of the zirconium balls are 5.5mm, 3.0mm, and 2.0mm, respectively, and the ratio is 2:5:3. The ball milling speed is 500 rpm, and the ball milling time is 12 hours. Then 0.1g of natural graphite (the weight ratio of solid dispersant to metal lithium is 5:1) is added to continue ball milling, the ball milling speed is 450 rpm, and the ball milling time is 2 hours. Then it is placed in a tubular furnace under an argon atmosphere for thermal stabilization and two-stage sintering treatment: first, the temperature is raised to 450℃ at a rate of 2℃ / min, and then the temperature is kept constant for 2h, and preheating and stabilization is performed; then the temperature is raised to 900℃ at a heating rate of 5℃ / min, and then the temperature is kept constant for 2h. After cooling to room temperature, the material was discharged to obtain a pre-lithiated silicon 2 oxide negative electrode material, which was recorded as D-1.
[0136] Comparative Example 2
[0137] The difference between this comparative example and Example 1 is that the metallic lithium is replaced with lithium stearate of equal mass as the lithium source; the rest of the process is the same as Example 1, and a pre-lithiated silicon 2 oxide negative electrode material is obtained, which is recorded as D-2.
[0138] Comparative Example 3
[0139] The difference between this comparative example and Example 1 is that only one carbon layer is coated by spray granulation, which specifically includes the following steps:
[0140] In an inert environment without water and oxygen, 2g of silicon dioxide powder and 0.02g of metal lithium ingot (the weight ratio of metal lithium to silicon dioxide powder is 1:100) are weighed and placed in a zirconium oxide ball milling jar, which is sealed and transferred to a planetary ball mill for ball milling. The ball-to-material ratio of the ball milling is 20:1, the diameters of the zirconium balls are 5.5mm, 3.0mm, and 2.0mm, respectively, and the ratio is 2:5:3. The ball milling speed is 500 rpm and the ball milling time is 12 hours. 0.2g of sodium carboxymethyl cellulose and 1.0g of asphalt (the weight ratio of carbon source to metal lithium is 60:1) are added, and 30g of solvent cyclohexane (the weight ratio of solvent to carbon source is 25:1) are added. The ball milling speed is 450 rpm and the ball milling time is 2 hours to obtain a mixed slurry, and the solid content in the mixed slurry is 10% by weight. The mixed slurry was spray granulated, with an inlet temperature of 180°C and an outlet temperature of 90°C. Argon gas was used as a carrier gas, with a carrier gas flow rate of 40L / min and a pressure of -0.05MPa to obtain a lithium-containing silicon oxide-based negative electrode material precursor. The lithium-containing silicon oxide material precursor was placed in a tubular furnace under an argon atmosphere for thermal stabilization and two-stage sintering treatment: first, the temperature was raised to 450°C at a rate of 2°C / min, and then kept at a constant temperature for 2h for preheating stabilization; then the temperature was raised to 900°C at a heating rate of 5°C / min, and then kept at a constant temperature for 2h. The pre-lithiated silicon oxide negative electrode material was obtained, which was recorded as D-3.
[0141] Example 2
[0142] In an inert environment without water or oxygen, 2g of silicon dioxide powder and 0.1g of lithium metal flakes were weighed and placed in a zirconium oxide ball mill (the weight ratio of lithium metal to silicon dioxide powder was 1:20), and then sealed and transferred to a nano ball mill for ball milling. The ball-to-material ratio of the ball milling was 20:1, the diameters of the zirconium balls were 5.5mm, 3.0mm, and 2.0mm, respectively, and the ratio was 2:5:3. The ball milling speed was 700 rpm, and the ball milling time was 24 hours. Then 0.2g of artificial graphite was added to continue the ball milling (the weight ratio of the solid dispersant to lithium metal was 2:1), the ball milling speed was 300 rpm, and the ball milling time was 1 hour. 0.2g sodium carboxymethyl cellulose and 1.0g asphalt (the weight ratio of carbon source to metal lithium is 12:1), and 30g solvent isopropanol (the weight ratio of solvent to carbon source is 25:1) are added, the ball milling speed is 450 rpm, the ball milling time is 2 hours, and a mixed slurry is obtained, and the solid content in the mixed slurry is 12% by weight. The mixed slurry is spray granulated, the inlet temperature is 180°C, the outlet temperature is 90°C, argon gas is used as carrier gas, the carrier gas flow rate is 30L / min, and the pressure is -0.05MPa, to obtain a lithium-containing silicon oxide-based negative electrode material precursor. The lithium-containing silicon oxide material precursor is placed in a tubular furnace under an argon atmosphere for thermal stabilization and two-stage sintering treatment: first, the temperature is raised to 450°C at a rate of 2°C / min for preheating stabilization, and then the temperature is kept constant for 2h; then the temperature is raised to 700°C at a heating rate of 5°C / min, and then the temperature is kept constant for 2h. After cooling to room temperature, the material was discharged to obtain a pre-lithiated silicon 2 oxide negative electrode material, which was recorded as F-2.
[0143] Example 3
[0144] In an inert environment without water or oxygen, 2g of silicon dioxide powder and 0.2g of metal lithium wire (the weight ratio of metal lithium to silicon dioxide powder is 1:10) are weighed and placed in a zirconium oxide ball milling jar, which is sealed and transferred to a nano ball mill for ball milling. The ball-to-material ratio of the ball milling is 20:1, the diameters of the zirconium balls are 5.5mm, 3.0mm, and 2.0mm, respectively, and the ratio is 2:5:3. The ball milling speed is 900 rpm and the ball milling time is 48 hours. Then 0.02g of artificial graphite is added for continued ball milling (the weight ratio of solid dispersant to metal lithium is 0.1:1), the ball milling speed is 450 rpm, and the ball milling time is 1 hour. 0.2g sodium carboxymethyl cellulose and 1.0g asphalt (the weight ratio of carbon source to metal lithium is 6:1), and 30g ethanol solvent (the weight ratio of solvent to carbon source is 25:1) are added, the ball milling speed is 450 rpm, the ball milling time is 2 hours, and a mixed slurry is obtained, and the solid content in the mixed slurry is 11% by weight. The mixed slurry is spray granulated, the inlet temperature is 180°C, the outlet temperature is 90°C, argon gas is used as a carrier gas, the carrier gas flow rate is 35L / min, and the pressure is -0.02MPa, to obtain a lithium-containing silicon oxide-based negative electrode material precursor. The lithium-containing silicon oxide material precursor is placed in a tubular furnace under an argon atmosphere for thermal stabilization and two-stage sintering treatment: first, the temperature is increased to 500°C at a rate of 2°C / min, and then the temperature is maintained for 2h, and preheating and stabilization is performed; then the temperature is increased to 800°C at a heating rate of 5°C / min, and then the temperature is maintained for 3h. After cooling to room temperature, the material was discharged to obtain a pre-lithiated silicon dioxide composite material, which was recorded as F-3.
[0145] Example 4
[0146] The difference between this embodiment and embodiment 1 is that:
[0147] Weigh 2 g of silicon dioxide powder and 0.04 g of lithium metal ingot (the weight ratio of lithium metal to silicon dioxide powder is 1:50);
[0148] Add 0.4 g of natural graphite (the weight ratio of solid dispersant to metallic lithium is 10:1);
[0149] Add 0.2 g of sodium carboxymethyl cellulose and 0.6 g of asphalt (the weight ratio of carbon source to metallic lithium is 20:1);
[0150] The remaining preparation conditions were the same as those in Example 1, and a pre-lithiated silicon 2 oxide negative electrode material was obtained, which was recorded as F-4.
[0151] Example 5
[0152] The difference between this embodiment and embodiment 1 is that:
[0153] In the two-stage sintering treatment of thermal stabilization: first, the temperature is raised to 300°C at a rate of 2°C / min, and then the temperature is kept constant for 2 hours for preheating stabilization; then the temperature is raised to 800°C at a rate of 4°C / min, and then the temperature is kept constant for 3 hours;
[0154] The remaining processes were the same as those in Example 1, and a pre-lithiated silicon 2 oxide negative electrode material was obtained, which was recorded as F-5.
[0155] Example 6
[0156] The difference between this embodiment and embodiment 1 is that:
[0157] The thermal stabilization treatment was carried out by a one-step sintering method. The negative electrode material precursor was placed in a tubular furnace under an argon atmosphere for thermal stabilization sintering. The calcination process was to increase the temperature to 900°C at a rate of 2°C / min and keep the temperature constant for 2h.
[0158] The remaining processes were the same as those in Example 1, and a pre-lithiated silicon 2 oxide negative electrode material was obtained, which was recorded as F-6.
[0159] Example 7
[0160] In an inert environment without water or oxygen, 2g of silicon dioxide powder and 0.02g of metal lithium ingot (the weight ratio of metal lithium to silicon dioxide powder is 1:100) are weighed and placed in a zirconium oxide ball milling jar, which is sealed and transferred to a planetary ball mill for ball milling. The ball-to-material ratio of the ball milling is 20:1, the diameters of the zirconium balls are 5.5mm, 3.0mm, and 2.0mm, respectively, and the ratio is 2:5:3. The ball milling speed is 500 rpm and the ball milling time is 12 hours. Then 0.1g of natural graphite (the weight ratio of solid dispersant to metal lithium is 5:1) is added and the ball milling is continued at a speed of 300 rpm for 5 hours. 0.2g sodium carboxymethyl cellulose and 0.4g asphalt (the weight ratio of carbon source to metal lithium is 30:1), and 60g solvent cyclohexane (the weight ratio of solvent to carbon source is 100:1) are added, the ball milling speed is 300 rpm, the ball milling time is 2 hours, and a mixed slurry is obtained, and the solid content in the mixed slurry is 4.5% by weight. The mixed slurry is spray granulated, the inlet temperature is 180°C, the outlet temperature is 90°C, argon gas is used as carrier gas, the carrier gas flow rate is 40L / min, and the pressure is -0.05MPa, to obtain a lithium-containing silicon oxide-based negative electrode material precursor. The lithium-containing silicon oxide material precursor is placed in a tubular furnace under an argon atmosphere for thermal stabilization and two-stage sintering treatment: first, the temperature is increased to 250°C at a rate of 2°C / min, and then the temperature is maintained for 3h, and preheating and stabilization is performed; then the temperature is increased to 900°C at a heating rate of 5°C / min, and then the temperature is maintained for 2h. After cooling to room temperature, the material was discharged to obtain a pre-lithiated silicon 2 oxide negative electrode material, which was recorded as F-7.
[0161] Example 8
[0162] The difference between this embodiment and embodiment 1 is that:
[0163] 0.2 g of polyvinyl alcohol and 1.0 g of phenolic resin (the weight ratio of carbon source to metal lithium is 60:1) were added, and 30 g of solvent tetrahydrofuran (the weight ratio of solvent to carbon source is 25:1) were added; the rest of the process was the same as in Example 1. A pre-lithiated silicon oxide negative electrode material was obtained, which was recorded as F-8.
[0164] The component contents, structural parameters and other data of the products obtained in the above examples and comparative examples are listed in the following Table 1.
[0165] Table 1
[0166]
[0167]
[0168] Test Case
[0169] This test example is used to illustrate the electrochemical performance of the products obtained in the examples and comparative examples when used as negative electrodes of lithium-ion batteries.
[0170] The products obtained in the examples and comparative examples were used as negative electrodes to assemble batteries, and their electrochemical performance was tested. The specific steps are as follows:
[0171] (1) Slurry preparation: weigh the negative electrode material, conductive agent, and binder in a ratio of 8:1:1, add solvent water to adjust the slurry viscosity, and stir for 3 hours.
[0172] (2) Coating: Use a doctor blade to coat the slurry on the copper foil current collector.
[0173] (3) Drying: Dry in a vacuum drying oven at 120°C for 12 h.
[0174] (4) Cutting: Cut the negative electrode into round pieces with a diameter of 15 mm, weigh them and place them in a drying oven.
[0175] (5) Assembly: In a glove box, CR2025 button cells were assembled using lithium sheets as counter electrodes.
[0176] The electrolyte was a 1M LiPF6 / EC:DMC (1:1, vol) mixed solution, and the separator was a Celgard 2300 polypropylene microporous membrane.
[0177] The sealed battery was left to stand for 24 hours, and the battery was subjected to charge and discharge test and cycle performance test using the Land battery performance test system. The test results are shown in Table 2.
[0178] Table 2
[0179]
[0180] According to the data in Table 2 above, we can see that:
[0181] Comparative Examples 1 to 3 omit steps or adjust the type of lithium source based on the preparation method of Example 1. Compared with Comparative Examples 1 to 2 and Comparative Example 4, Example 1 adopts the method provided by the present invention to prepare the negative electrode material F-1. When F-1 is used for the battery negative electrode, a higher first coulombic efficiency and cycle capacity retention rate can be obtained.
[0182] The battery assembled by directly using conventional silicon oxide without pre-lithiation as the negative electrode material has an initial coulombic efficiency of about 69%, and a capacity retention rate of about 100 cycles of about 16%. Compared with silicon oxide as the negative electrode material, the negative electrode materials F-1 to F-8 prepared by the method provided in the present disclosure in Examples 1 to 8 can obtain higher initial coulombic efficiency and cycle capacity retention rate when F-1 to F-8 are used as the negative electrode of the battery.
[0183] The addition ratios of the raw materials in Example 4 are all within the optimized range provided in the present disclosure. Compared with F-1 prepared in Example 1, when F-4 prepared in Example 4 is used as a battery negative electrode, a higher first coulombic efficiency and cycle capacity retention rate can be obtained.
[0184] The conditions of the two-stage sintering treatment in Example 5 are within the optimized range provided in the present disclosure. Compared with F-1 prepared in Example 1, when F-5 prepared in Example 5 is used as a negative electrode of a battery, a higher first coulombic efficiency can be obtained.
[0185] In Example 6, a one-step sintering method is used for heat stabilization treatment. Compared with F-6 prepared in Example 6, when F-1 prepared in Example 1 is used as a battery negative electrode, a higher first coulombic efficiency and cycle capacity retention rate can be obtained.
[0186] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0187] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0188] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing a pre-lithiated silicon oxide-based negative electrode material, characterized in that: The following steps are involved: (1) contacting metallic lithium with silicon oxide powder and performing solid phase homogenization to obtain a first product; (2) dispersing and homogenizing the first product with a solid dispersant to obtain a second product; (3) contacting the second product with a carbon source and a solvent and performing a mixing and homogenization treatment to obtain a mixed slurry; (4) subjecting the mixed slurry to a spray granulation process to obtain a third product; (5) subjecting the third product to a thermal stabilization treatment; The above steps (1) to (5) are carried out in an inert atmosphere.
2. The method according to claim 1, characterized in that In step (1), the weight ratio of the metallic lithium to the silicon dioxide powder is 1:1 to 100, preferably 1:20 to 100; Optionally, the metallic lithium is selected from one or more of lithium ingots, lithium wires, lithium powders and lithium sheets; Optionally, the average particle size of the silicon oxide powder is 0.1 to 20 μm.
3. The method according to claim 1, characterized in that In step (1), the solid phase homogenization treatment method includes mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser; Optionally, the conditions for the solid phase homogenization treatment include: a ball milling speed of 300 to 2000 r / min, a ball milling time of 6 to 72 h, and a ball-to-material ratio of 1 to 20:1; preferably, the ball milling speed is 500 to 1000 r / min, the ball milling time is 6 to 48 h, and the ball-to-material ratio is 10 to 20:
1.
4. The method according to claim 1, characterized in that In step (2), the weight ratio of the solid dispersant to metallic lithium is 0.1 to 50:1, preferably 5 to 10:1; Optionally, the solid dispersant is selected from one or more of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon and soft carbon.
5. The method according to claim 1, characterized in that In step (2), the dispersion and homogenization treatment method includes mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser; Optionally, the conditions for the dispersion and homogenization treatment include: a ball milling speed of 50 to 500 r / min, a ball milling time of 0.5 to 12 h, and a ball-to-material ratio of 1 to 20:1; preferably, the ball milling speed is 100 to 300 r / min, the ball milling time is 3 to 8 h, and the ball-to-material ratio is 10 to 20:
1.
6. The method according to claim 1, characterized in that In step (3), the carbon source is selected from a carbonizable organic carbon source; the weight ratio of the carbon source to metallic lithium is 1 to 60:1, preferably 10 to 30:1; The weight ratio of the solvent to the carbon source is 10 to 100:1, preferably 50 to 100:1; Optionally, the solid content of the mixed slurry is 1 to 30% by weight, preferably 5 to 15% by weight; Optionally, the carbonizable organic carbon source is selected from one or more of a polymer carbon source, a petroleum carbon source, a sugar carbon source, a graphite carbon source and other carbon sources; The polymer carbon source includes one or more of phenolic resin, epoxy resin, polyvinyl pyrrolidone and polyvinyl alcohol; The petroleum carbon source includes one or more of asphalt, petroleum coke and needle coke; The sugar carbon source includes one or more of glucose, sucrose and fructose; The other carbon source is selected from one or more of sodium carboxymethyl cellulose, polyvinyl alcohol and carboxy styrene butadiene latex; preferably one or more of sodium methyl cellulose and polyvinyl alcohol; The solvent is selected from one or more of ethanol, isopropanol, n-butanol, cyclohexane and cyclohexanone.
7. The method according to claim 1, characterized in that In step (3), the mixing and homogenizing treatment method includes mechanical homogenization, and the mechanical homogenization is selected from any one of a ball mill, a sand mill, a homogenizer and a disperser; Optionally, the conditions for the mixing homogenization treatment include: a ball milling speed of 50 to 500 r / min, a ball milling time of 0.5 to 24 h, and a ball-to-material ratio of 1 to 20:1; preferably, a ball milling speed of 100 to 300 r / min, a ball milling time of 0.5 to 3 h, and a ball-to-material ratio of 10 to 20:
1.
8. The method according to claim 1, characterized in that: In step (4), the conditions of the spray granulation treatment include: an inlet temperature of 100 to 300° C., an outlet temperature of 50 to 200° C., a carrier gas flow rate of 10 to 100 L / min, and a pressure of -0.1 to -0.05 MPa; Preferably, the inlet temperature is 120 to 240°C, the outlet temperature is 80 to 150°C, the carrier gas flow rate is 30 to 60 L / min, and the pressure is -0.08 to -0.05 MPa; The carrier gas is selected from one or more of argon, nitrogen and helium; Preferably, the average particle size of the third product obtained by spray granulation is 5 to 50 μm.
9. The method according to claim 1, characterized in that: In step (5), the thermal stabilization treatment includes a multi-stage sintering treatment; Preferably, the thermal stabilization treatment comprises a first stage sintering treatment and a second stage sintering treatment performed sequentially; The conditions of the first stage sintering treatment include: heating to 200-500°C at a heating rate of 1-5°C / min, and then maintaining the temperature for 1-6 hours; the conditions of the second stage sintering treatment include: heating to 600-1200°C at a heating rate of 2-5°C / min, and then maintaining the temperature for 1-12 hours; Preferably, the conditions for the first sintering treatment include: heating to 250-400°C at a heating rate of 2-3°C / min, and then maintaining the temperature for 2-3 hours; the conditions for the second sintering treatment include: heating to 700-900°C at a heating rate of 3-5°C / min, and then maintaining the temperature for 2-6 hours.
10. A pre-lithiated silicon oxide-based negative electrode material prepared according to the method of any one of claims 1 to 9.
11. A pre-lithiated silicon oxide-based negative electrode material, characterized in that: The pre-lithiated silicon oxide-based negative electrode material comprises pre-lithiated silicon oxide-based particles with a core-shell structure; the pre-lithiated silicon oxide-based particles comprise a core and a first carbon layer and a second carbon layer sequentially coated from the inside to the outside on the outer surface of the core, wherein the first carbon layer and the second carbon layer form an outer shell of the core-shell structure; The core comprises a silicon oxide matrix and a core lithium-containing component dispersed on the surface and in the pores of the silicon matrix; the core lithium-containing component comprises lithium silicate.
12. The pre-lithiated silicon oxide-based negative electrode material according to claim 11, characterized in that: The first carbon layer comprises a first lithium-containing component, and the second carbon layer is lithium-free; the lithium content in the core is greater than the lithium content in the first carbon layer; Preferably, the content of the lithium-containing component in the pre-lithiated silicon oxide-based particles is 0.01 to 10% by weight, preferably 0.1 to 6% by weight, based on the total amount of lithium element; Optionally, the core lithium-containing component further comprises metallic lithium; The first lithium-containing component comprises one or more of metallic lithium, lithium oxide and lithium-carbon alloy.
13. The pre-lithiated silicon oxide-based negative electrode material according to claim 11, characterized in that: Based on the total weight of the pre-lithiated silicon dioxide-based particles, the content of the inner core is 50 to 95% by weight, preferably 60 to 90% by weight; the total content of the outer shell is 5 to 50% by weight, preferably 5 to 40% by weight.
14. The pre-lithiated silicon oxide-based negative electrode material according to claim 11, characterized in that: The average particle size of the pre-lithiated silicon oxide-based particles is 0.5 to 30 μm, and the BET specific surface area is 0.1 to 100 m 2 / g, total pore volume is 0.001~0.5cm 3 / g; Optionally, the total thickness of the first carbon layer and the second carbon layer is 10-1000 nm; preferably, the thickness of the first carbon layer is 10-500 nm, and the thickness of the second carbon layer is 40-100 nm.
15. A negative electrode of a lithium-containing battery, characterized in that: The invention comprises the pre-lithiated silicon oxide-based negative electrode material as described in any one of claims 10 and 11 to 14.
16. A lithium-containing battery, characterized in that: Comprising the negative electrode as claimed in claim 15.
